Comprehensive evaluation of land reclamation and utilisation schemes based on a modified VIKOR method for surface mines. Issue 2 (17th February 2018) - Zhou, Wei; Yin, Wenying; Peng, Xiaoqing; Liu, Fuming; Yang, Fei
Abstract: In view of the significance of evaluating reclamation schemes for surface mines, the authors propose an integrated evaluation method based on multi-attribute decision-making theory. An evaluation index system incorporating local conditions was constructed. Triangular fuzzy theory was applied to consider the fuzziness of indexes. Weights were calculated by combining the analytic hierarchy process and entropy method to reduce the influence of original data and subjective and objective factors. The programmes were sorted by the modified VIKOR method. Finally, farming, forestry and grass–animal husbandry schemes were evaluated for the Xiaolongtan surface mine to verify the effectiveness of the proposed approach.